Pemberdayaan Masyarakat Pesantren Ar-Rahmah, Rejang Lebong dalam Memanfaatkan Lahan Pekarangan dengan Budi Daya Bawang Merah - Marlin Marlin; Antoni Sitorus; Muhamad Solihin; Atra Romeida; Reny Herawati (Institut Pertanian Bogor, 2020)
The community empowerment in the area of Ar-Rahmah pesantren, Air Meles Atas Village, Rejang Lebong Regency, Bengkulu was intended to increase the income of pesantren to finance poor students, and at the same time to enhance the ability of pesantren in carrying out educational and teaching activities. Community service activities carried out in the form of assistance activities in shallot cultivation in the yard of the Ar-Rahmah Pesantren. The assistance program is carried out for 4 months, with such stage of activities as: the preparation stage for managers, teachers, students and farmers around the pesantren, seed selection, land preparation, planting, maintenance, harvesting, and post-harvest. The evaluation result showed that the community participation and involvement in the shallot cultivation assisting program were considered high. The highest participation rates were during the selection of seed activity (73%) and planting activity (100%). Meanwhile, the lowest participation rate was during maintenance activities (27%). The evaluation results showed the level of participants’ satisfaction is high (90‒100%) on the implementation of assistance activities. The harvested shallots could increase the income of the boarding school which can be used to help the education cost and education progress of the boarding school. The participation of the entire community would be encouraged so that the success of empowerment program could be felt by the entire community. The community empowerment program need to be carried out continuously, so it would enhance the welfare of and self-sufficiency of the community.